Las técnicas y estrategias didácticas que utilizan los docentes en el proceso de enseñanza - aprendizaje del idioma inglés y su incidencia en el logro de las destrezas con criterio de desempeño en los estudiantes de octavo, noveno y décimo año de educación general básica de la parroquia La Asunción, del cantón Girón período 2011-2012”. Lineamientos alternativos - Cartuche Soto, Noemí Esperanza (2015)
The present investigation called "TEACHING TECHNIQUES AND STRATEGIES USING THE TEACHERS IN THE TEACHING - LEARNING ENGLISH LANGUAGE AND ITS IMPACT ON THE ACHIEVEMENT OF SKILLS WITH STANDARD OF STUDENT PERFORMANCE IN EIGHTH, NINTH AND TENTH YEAR OF EDUCATION GENERAL BASIC ASSUMPTION PARISH, CANTON GIRÓN PERIOD 2011-2012 ".- ALTERNATIVE GUIDELINES". .You General objective: To determine the didactic techniques and strategies used by teachers and their impact on the teaching and learning of English Language students-leading eighth, ninth, tenth year of Basic Education Technical College "Remigio Crespo Toral "during 2012-2013. It was a kind of descriptive research methods were used: scientific, inductive, deductive, hypothetical deductive and statistical. Within the methodological survey process was applied to 15 teachers and 105 students from eighth to tenth year of General Basic Education, for information collection and subsequent contrasting with the hypothesis, establishing the problems arising. After processing the information collected data it was determined that the techniques and teaching strategies are directly related to the procedures activities and methods in college students' Remigio Crespo Toral "and the pedagogical processes that take place are always oriented by 81%, through the application of techniques and teaching strategies.